The effect of TARP on loan loss provisions and bank transparency - Kim, Jinyong; Kim, Mingook; Lee, Jeong Hwan (Journal of Banking & Finance, 2019)
We empirically investigate the effect of the Capital Purchase Program under the Troubled Asset Relief Program (TARP) on the transparency of participating banks by examining changes in their loan loss provisions. We demonstrate that TARP banks reduced transparency to a greater extent than non-TARP banks did by recognizing smaller and less timely loan loss provisions for changes in nonperforming loans and increasing discretionary loan loss provisions more after receiving TARP funds. While the reduced timeliness was mainly observed in large TARP banks and banks with low tier 1 capital or high earnings, small TARP banks and banks with low earnings significantly increased their discretionary provisions. In addition, the decreased timeliness and increased discretionary provisions were mainly driven by TARP banks that did not repay their funds. TARP banks’ reduced transparency, which inhibits the accurate assessment of bank risk by outsiders, is consistent with moral hazard in disclosing their financial reporting information.